Penggunaan Media Clay Dalam Menstimulus Perkembangan Motorik Halus Anak Usia Dini - Anisa Anisa; Andi Rezky Nurhidaya; Abdul Hakim Naba (PG PAUD Universitas Islam Makassar | LP2M-UIM | PPJ PAUD (Perhimpunan Pengelola Jurnal PAUD) Indonesia, 2025)
Fine motor development proficiency is a crucial prerequisite for young children to support writing readiness. However, most Group A children at RA Prestasi Ummi Annurah were identified as experiencing finger muscle stiffness, quick fatigue during hand-based physical activities, and limited visual-motor control during coloring. This study aims to analyze the implementation of structured learning using homemade flour clay and describe the forms of changes in children's fine motor performance following the intervention. A qualitative approach with a descriptive method was applied. The research subjects consisted of 15 Group A children (aged 4–5 years), with the classroom teacher and school principal serving as supporting informants. Data collection procedures were conducted through multisource techniques including passive participant observation, in-depth interviews, and documentation of children's portfolios. The data analysis technique adopted the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The results showed that utilizing flour clay through a guided play model, which actively involves children from the dough-making stage to forming universe objects, is highly effective in stimulating the intrinsic hand muscles. The identified forms of development include the transition of pencil grip to an efficient tripod grip, firm and stable strokes when copying numbers 1–5, and increased line control precision during coloring activities. This research contributes to providing a practical methodological reference for early childhood educators in utilizing economical sensory-manipulative media for holistic child motor stimulation.